A gift of hope [compact disc, unabridged] : helping the homeless - Steel, Danielle (Brilliance Audio, 2012)
Since the devastating loss of her son, Danielle Steel has been dedicated to helping the homeless of San Francisco - taking to the streets herself with a small team of friends to directly provide much needed resources, from food and clothing to bedding and toiletries. Now, the notoriously private author is offering a gift far more enduring - that of her voice, in a heartfelt call for more effective action to aid this vast, tragic population. Here is the eye-opening story of her personal work over more than a decade with the most destitute members of our society, and how it has enriched her life beyond all of her material successes. Inspirational, raw, and deeply moving, A Gift of Hope is not to be missed.